Splenic rupture and intracranial haemorrhage in a haemophilic neonate: Case report and literature review - Ibrahim Adamu; Armand Asarian; Philip Xiao (Wolters Kluwer Medknow Publications, 2012)
Splenic rupture and intracranial haemorrhage are life-threatening conditions infrequently encountered in neonates without history of birth trauma. External manifestations of birth trauma; namely, capput succadeneum and cephalhematoma, when present raise suspicions for more serious intracranial or visceral damage. Rupture of normal spleen without an obvious source of trauma in haemophilic neonate is a rare event. The concurrence of both conditions and the unusual presentation make this case a rare one that is seldom encountered in the literature. Additionally, when splenic rupture occurs, the consensus is to employ all non-operative techniques aimed at salvaging the spleen, thus avoiding the immune-compromised state associated with splenectomy. However, in this case, we present a 3-day-old male with family history of haemophilia A, who was diagnosed with splenic rupture and bilateral subdural haematomas and underwent splenectomy, albeit with post-operative complications, in light of haemodynamic instability and high ongoing transfusion requirements.